2022
DOI: 10.1515/freq-2021-0189
|View full text |Cite
|
Sign up to set email alerts
|

An RHCP and LHCP polarization reconfigurable microstrip antenna for ISM band smart city applications

Abstract: In this article, a microstrip antenna having circular polarization switching capability is presented. This antenna consists of a circular-shaped radiating patch with a single co-axial probe feed line. The polarization reconfigurability is achieved by introducing four symmetrical U-shaped slots and silicon PIN diodes on the radiating patch. A prototype of the design is fabricated on an FR-4 substrate with overall dimension of 70 × 70 × 1.6 mm to verify the performances. The measured results of the antenna exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Also, copper addition is an excellent technique for achieving highest yields [12] reported that generally the growth of Aspergillus species is less affected by the presence of Cu 2+ than Rhizopus species, with the most resistant strain to the copper ions inhibition being Aspergillus niger. [15] also found that copper ions play an important role in minimizing the deleterious effects of iron on citric acid production.…”
Section: Effect Copper Ion Concentrations On Citric Acid Productionmentioning
confidence: 92%
See 1 more Smart Citation
“…Also, copper addition is an excellent technique for achieving highest yields [12] reported that generally the growth of Aspergillus species is less affected by the presence of Cu 2+ than Rhizopus species, with the most resistant strain to the copper ions inhibition being Aspergillus niger. [15] also found that copper ions play an important role in minimizing the deleterious effects of iron on citric acid production.…”
Section: Effect Copper Ion Concentrations On Citric Acid Productionmentioning
confidence: 92%
“…When the copper ion level is in the right proportion together with operational parameter, the medium will allow high production of citric acid. Copper ion is known to have chelating effect and also been used as an antagonist to iron [14,15]. Furthermore, copper ion addition also provide the advantage of selectively inhibits Penicillia growth as a contaminant [16].…”
Section: Introductionmentioning
confidence: 99%